MODERN APPROACHES TO STRATEGIC HUMAN CAPITAL MANAGEMENT IN THE IT SECTOR - SKLIARUK, Tetiana; TURKO, Vasyl (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive exploration of the evolution of the concept of human capital and its critical role in modern management practices, with a particular focus on the Information Technology (IT) sector. Over time, human capital has evolved from an economic consideration to a strategic asset that shapes organizational success in the knowledge-driven economy. The article examines various key academic approaches to human capital management, including the resource-based view, investment theory, talent management frameworks, digital competency development, and the growing importance of analytical and social approaches.The authors argue that effective human capital management within IT companies is crucial for achieving long-term competitive advantages and ensuring sustainable growth. Talent is seen not just as a resource but as a driving force for innovation, adaptability, and success in high-tech industries. Special attention is given to practices for attracting, developing, and retaining IT talent, with an emphasis on digital skills, HR analytics, and social capital in the context of digital transformation.A comparative analysis of human capital management approaches is presented, offering insights into how these strategies can be applied to enhance decision-making within IT companies. This serves as an analytical tool for improving strategies, boosting performance, and staying ahead of industry trends. The study also discusses the impact of globalization and technological advancements on workforce mobility and human capital management, offering perspectives on the integration of digital competencies into the future workforce and managing talent across borders.The article highlights several research opportunities, particularly regarding the integration of digital skills into human capital strategies and the effects of workforce mobility, which will be essential for shaping future human capital management practices.
Keywords: human capital; strategic management; IT sector; digital competencies; talent management; resource-based approach; HR analytics